Environment-sensitive turn-on fluorescent probe enables live cell imaging of myeloperoxidase activity during NETosis - Enebie Ramos Cáceres; Lotte Kemperman; Kimberly M. Bonger (Communications Chemistry)
Abstract Myeloperoxidase (MPO) plays an important role in the immune response of human neutrophils and has been implicated in autoimmune conditions, cardiovascular disorders, and neurodegeneration. Current methods to detect MPO activity rely on the detection of HOCl using activatable probes or require challenging experimental procedures. Therefore, these tools provide limited information about the dynamics and localization of MPO in complex molecular processes such as NETosis in real time. In this study, we report a ‘’turn-on” activity-based probe that fluoresces exclusively upon binding to MPO, exhibits minimal background fluorescence in buffered aqueous media, and is blocked by MPO inhibitors. Our probe facilitates real-time imaging of direct MPO activity in human neutrophils and HL-60-derived granulocytes during NETosis under wash-free conditions. Furthermore, it allows for the discrimination between different triggers of NETosis in human neutrophils. These findings hold promise for advancing our understanding of the role of MPO in immune responses and inflammatory conditions.